Współpraca cywilno-wojskowa NATO w regionalnym systemie bezpieczeństwa: CIMIC w reagowaniu kryzysowym i obronie kolektywnej .......... 109 - Mazurkiewicz, Agata (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
Civil-military cooperation (CIMIC), as an institutionalized military function within NATO, was established after the experiences gathered by the Alliance during conflicts in the Balkans. Its main purpose is to support the NATO commander and his mission by coordinating activities and communicating with various civilian entities present in the area of NATO operations (e.g. international organizations, local population and authorities). As such, CIMIC was primarily designed to support Alliance troops in NATO’s out-of-area operations. Along with the gradual withdrawal of the Alliance from such operations, grew the prominence of questions regarding the use of CIMIC under the Art. 5 of the Washington Treaty. This chapter aims to analyse the potential and possibilities of civil-military cooperation in the framework of collective defence, as well as diagnose the main challenges in this regard.